“Moria is more dangerous than Afghanistan.”: a critical approach towards greek asylum and migration policies - Felix, Claire (2021)
Greece has faced in a first time the consequences of the financial crisis in 2007 which led to several austerity measures, bailout packages from the EU and numerous revolts from its population. Some years later, in 2015, the country was then confronted to the ‘refugee crisis’, bringing hundreds and thousands of individuals seeking international protection. Migration and asylum policies have been implemented, targeting the decrease of irregular migrants’ venue. In this context, the main objective is to identify the influence of migration and asylum policies on the everyday life of asylum seekers and locals. Two periods of fieldwork in Greece have been conducted. The first one occurred in Eleonas, the refugee camp of Athens, between August 2019 and January 2020. The second one took place on the island of Lesvos during the month of February 2020, where the Hotspot Moria is situated. Thus, participant observation and fieldnotes, semi-structured interviews, surveys and literature analyses were the methods used. The results indicate that policies are rather exclusionist and perpetuate the imposed categorization of individuals, be it asylum seekers and Greeks. In particular, asylum procedures are driven by humanitarian governance, governmentality, and bio-power, in other words, holding power over the life of asylum seekers and locals. This thesis calls also for more inclusive policies between asylum seekers and locals.